Serum lipids, leptin, and soluble leptin receptor in alcohol dependence: A cross-sectional and longitudinal study - Weinland, Christian; Tanovska, Petya; Kornhuber, Johannes; Mühle, Christiane; Lenz, Bernd (Drug and Alcohol Dependence, 2020)
Objective: Alcohol dependence affects metabolic processes. Further research is needed to apply this knowledge clinically. In this study, possible differences in serum lipids and/or leptin activities between alcohol-dependent in-patients and healthy controls and possible associations with alcohol-related blood parameters and with prospective outcomes in alcohol dependence were assessed sex-specifically.
CRIS-Team WoS Importer:2020-05-08